LNG shipping chokepoints: The impact of red sea and panama canal disruption - Jack Sharples (The Oxford Institute for Energy Studies, 2024)
With droughts restricting shipping via the Panama Canal since mid-2023, the attacks on vessels in the Red Sea have caused a complete cession in LNG shipping between Europe and Asia via the Suez Canal. This disruption primarily affects LNG supply from the United States, Qatar, Russia, and North Africa. While some cargoes are being diverted to alternative markets, other cargoes are being re-routed via the Cape of Good Hope. The longer round-trips are effectively curtailing LNG shipping capacity, but even if the disruption continues for the whole of 2024, the impact will be a year-on-year reduction in global LNG supply of 1.35 per cent, which explains the lack of reaction from European and Asian LNG benchmark prices. Looking ahead, the cumulative impact of longer shipping times will grow, but will be offset in the second half of 2024 by new LNG supply from West Africa and the re-opening of the Panama Canal after the rainy season.
Keywords: 330; Asia; Europe; LNG; Panama Canal; Qatar; Red Sea; Russia; United States